Incidence of diabetes mellitus following hospitalisation for COVID-19 in the United Kingdom: a prospective observational study - Tyrer,F; Gharibzadeh,S; Gillies,C; Lawson,C; Routen,A; Islam,N; Razieh,C; Zaccardi,F; Yates,T; Davies,MJ; Brightling,CE; Chalmers,JD; et al. (Diabetes, Obesity and Metabolism: a journal of pharmacology and therapeutics, 2025)
BackgroundPeople hospitalised for coronavirus disease 2019 (COVID-19) have elevated incidence of diabetes. However, it is unclear whether this is due to shared risk factors, confounding or stress hyperglycaemia in response to acute illness.MethodsWe analysed a multicentre prospective cohort study (PHOSP-COVID) of people ≥18 years discharged from NHS hospitals across the United Kingdom following COVID-19. Individuals were included if they attended at least one research visit with a HbA1c measurement within 14 months of discharge and had no history of diabetes at baseline. The primary outcome was new onset diabetes (any type), as defined by a first glycated haemoglobin (HbA1c) measurement ≥6.5% (≥48 mmol/mol). Follow-up was censored at the last HbA1c measurement. Age-standardised incidence rates and incidence rate ratios (adjusted for age, sex, ethnicity, length of hospital stay, body mass index, smoking, physical activity, deprivation, hypertension, hyperlipidaemia/hypercholesterolaemia, intensive therapy unit admission, invasive mechanical ventilation, corticosteroid use and C-reactive protein score) were calculated using Poisson regression. Incidence rates were compared with the control groups of published clinical trials in the United Kingdom by applying the same inclusion and exclusion criteria, where possible.ResultsIncidence of diabetes was 91.4 per 1000 person-years and was higher in South Asian (incidence rate ratios [IRR] = 3.60; 1.77, 7.32; p < 0.001) and Black ethnic groups (IRR = 2.36; 1.07, 5.21; p = 0.03) compared with White ethnic groups. When restricted to similar characteristics, the incidence rates were similar to those in UK clinical trials data.ConclusionDiabetes incidence following hospitalisation for COVID-19 is high, but it remains uncertain whether it is disproportionately higher than pre-pandemic levels.